Examining the moderating effect of perceived risk from particulate matter on outdoor sports participants: a theory of planned behavior perspective - Kim, Do Hun; Jeong, Yunduk (Frontiers in Public Health, 2024)
Purpose -This study, drawing from the theoretical framework of the Theory of Planned Behavior (TPB), examines the structural relationship among attitudes, subjective norms, perceived behavioral control (PBC), and behavioral intention. The study focuses on investigating how the perceived risk associated with particulate matter moderates the relationships between 'attitudes and behavioral intention,' 'subjective norms and behavioral intention,' and 'PBC and behavioral intention' within the context of individuals engaged in outdoor sports.Design/methodology/approach -The data were collected from outdoor sports gatherings facilitated through a popular South Korean sports meetup application.Confirmatory factor analysis was employed to establish the construct validity of the measurement scale, assess factor loadings, averaged variance extracted (AVE), and construct reliability (CR). We also ensured the reliability of the measurement scale through Cronbach's α analysis. To achieve our research objectives, we utilized structural equation modeling with maximum likelihood estimation to examine the positive relationships under investigation. Additionally, we performed moderation analysis using the statistical software Jamovi.Findings -The findings demonstrate the significant impacts of attitudes, subjective norms, and PBC on behavioral intention and reveal that perceived risk acts as a moderator, influencing the relationship between PBC and behavioral intention.